Employing secondary schools leaders for information and communications technology and its effect on organizational culture in Al-Medina - Abutarboush, Omneyah Abdullah (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the degree of using of ICT (Hardware, Software & Databases, Human Resources and communication networks) relationship and organizational culture (organizational values, organizational beliefs, organizational norms, organizational expectations) in secondary schools for girls in Madinah.The study relied on a descriptive method, and the sample of this study is the same as population of 144 person (56 leaders) and (88 Agents). The questionnaire was used as tool for data collection. The study found the degree of employing ICT in Madinah secondary schools was high from educational leaders’ point of view. ICT helps School Administration in Madinah secondary school in improving organizational culture was high. The study indicated there were statistically significant differences in the view of the respondents about the relationship between ICT and organizational culture in Madinah secondary school. The study recommends in this study: The important of involve educational leaders in creating, implemented and apply the administrative technology program, develop the ICT programs to be one completed program construct all educational services, Built strong organizational culture in schools.
Keywords: Information and Communications Technology (ICT); Organizational Culture